Two species representing a new genus of microascaceae, from Venezuela - Delgado ívilaAdolfredo; Piñeiro Chávez, Albino; Urdaneta García, Lilia (Revista Científica de la Facultad de Ciencias Veterinarias)
During a continuing study of coprophilous fungi in Venezuela, a new genus, Lophotrichus, including two especies L. ampullus and L. bartlettii, is described, which has certain characteristics of the microascaceae pyrenomycete with two germ pores. The two described species of this genus are discussed here: Lophotrichus ampullus isolated from goat, fox, hen, dog, turkey, horse, cow, calf, and turtles dungs, L. bartlettii from horse, calf, donkey, rabbit, fox, hen, cat and deer dungs. These two identified species represents new records for Venezuela.